Reform der Erdgaswirtschaft in der EU und in Deutschland: Wie viel Regulierung braucht der Wettbewerb? - Christian R. von Hirschhausen; Thorsten Beckers (Deutsches Institut für Wirtschaftsforschung (DIW), 2004)
This article analyses the reform process in the European and the German natural gas sector. Competition in the industry and intra-European trade have been underdeveloped thus far. We argue that the European gas pipelines are a monopolistic bottleneck that require some form of access regulation, e.g. in the form of an Entry-Exit System. We discuss how regulation should be implemented at the European level and, subsequently, in Germany. We conclude that the European Gas Directive 2003/55/EC and the proposal for a new Energy Law in Germany offer a good point of departure for further reforms towards an integrated European market for natural gas.
Keywords: 330